Pokémon : Ash's Big Challenge [anglicky] / Book 1 - West, Tracey, 1965- (Orchard Books, 2021)
Pokémon master-in-training Ash Ketchum has been sent on a very important mission - to capture a unique and mysterious Poké Ball. Ash and his friends must journey to the famed Orange Islands for their biggest Pokémon adventures yet.